Training intensity distribution and changes in performance and physiology of a 2nd place finisher team of the Race across America over a 6 month preparation period - Manunzio, C.; Mester, J.; Kaiser, W.; Wahl, P. (Frontiers in Physiology, 2016)
Aim: To monitor the training intensity distribution (TID) and the development of physiological and performance parameters.